Pattern of Cystoid Macular Edema - Joma, .Ahmed Kareem (AL-Kindy College Medical Journal, 2016)
Background: Cystoid Macular Edema (CME) in its various forms can be considered one of the leading causes of central vision loss in the developed world. It is not a disease itself, It represents a common pathologic sequel of the retina and occurs in a variety of pathological conditions such as, diabetic retinopathy, central or branch retinal vein occlusion(CRVO,BRVO), intraocular inﬂammation and following cataract extraction. Objective: This study was done to investigate the pattern of CME in patient attending Erbil Teaching Hospitals.Type of the study: Cross- sectional study.Methods and Materials: This is a hospital base cross- sectional study that included 61 patients (75 eyes) conducted at Erbil Teaching Hospitals for six months. All patients underwent a comprehensive assessment including medical and ophthalmic history, detailed ophthalmic examination and Optical Coherence Tomography (OCT) examination.Results: of the 61 patients 32 (52.5%) were females and 29 (47.5%) were males. The mean age was (56.4±10.8) years. Out of the 75 eyes included in the study, 41 eyes (54.66%) had diabetic retinopathy, 10 eyes (13.34%) had CME following cataract operation (Irvine-Gass syndrome), 8 eyes (10.67%) had BRVO, 6 eyes (8%) were had CRVO, 5 eyes (6.66%) had age related macular degeneration, 3 eyes (4%) with uveitis, and 2eyes (2.67%) had Retinitis Pigmentosa. The average macular thickness was (415.6± 107).Conclusions: Diabetic retinopathy is the most common predictive factor of CME, followed by cataract surgery. CME is more severe in diabetic retinopathy, CRVO and after cataract surgery.